Digital Government for Anti Corruption: A Systematic Literature Review - Kisman Karinda; Andi Agustang; Arifuddin Usman (GoAcademica Research & Publishing, 2023)
Corruption is a major crime that harms state finances and the public interest. One way to fight corruption is to implement digital government to increase government transparency and accountability. The purpose of this study was to undertake a thorough review of the literature on government digitalization and anti-corruption.This study used a descriptive analysis approach to 99 articles obtained from the Scopus database in the 2019-2021 period. The data in the form of RIS is processed by using VOSviewer which showed that Government, Transparency, Corruption, Governance and Level are the most dominant concepts that are most often explained by researchers. This indicated that these four keywords have a very significant influence in studies on this topic. This research contributed to providing a reference for policy makers or relevant stakeholders in preventing corrupt practices through the application of digital government which is increasingly important during Covid-19. The limitation of this study lied in the reference source which only comes from Scopus and the short duration of data collection. Therefore, in order to produce a comparative, broad and comprehensive analysis, further studies need to include sources of other reputable international journals such as the Web of Science (WoS) and increase the duration of data collection.